Covid-19 Vaccine Acceptance, Intention to Participate and its Associated Adverse Events Happening among the Vaccinated Population of Lahore, Pakistan - Almina Shafiq, Madiha Asghar, Qurat Ul Ain, Sania Maqbool, Rabia Aslam, Sana Mehmood, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: This cross-sectional study being instrumented by a close ended questionnaire was conducted to evaluate society’s affirmation for being jabbed with COVID-19 vaccine, their acquisition towards immunization and associated anomalies in vaccinated people. According to the recent update from WHO, the glob is facing 5th wave of pandemic “Omicron”. However, the problem is that vaccines were in trials. Majority of people were demonstrating reluctance for being immunization against COVID-19 due prevailing oddities after vaccination. Aim: To measure the possible adverse effects caused by the vaccination and society’s participation towards immunization. Methodology: In this study we adapted cross sectional study design by means of convenience sampling. Study instrument was a close ended questionnaire. Data was collected from only vaccinated participants by visiting universities, medical personnel, colleges and other society sectors under the supervision of team members. Data transferred to software SPSS to extract the results. Cross tabulation was used for demographic analysis such as age, gender and vaccine type jabbed. Results: The most common adverse effects include inflammation at site of injection, fever, nausea and vomiting, diarrhea, abdominal pain, joint pain and numbness of limbs were highlighted. Mostly jabbed vaccine types include Sinopharm and Sinovac. Majority of respondents showed willingness for immunization however, only a small proportion was afraid for being vaccinated. The significance in our study that we have conducted study for acceptance of vaccine, intention of participants towards immunization and adverse events associated with different types of COVID-19 vaccines in vaccinated population residing in different towns of Lahore, Pakistan. Conclusions: In our local population, majority accepted the vaccine and didn’t deny to administer the vaccine. Pain, redness, lethargy, nausea, vomiting, diarrhea, abdominal pain, numbness and arthritis were noted to be the most common side effects of COVID- 19 vaccine. Keywords: COVID-19, Vaccine Acceptance, Pakistan Vaccinated Population